The Effectiveness of Anticholinergic Therapy for Overactive Bladders: Systematic Review and Meta-Analysis - Andrea Moura Rodrigues Maciel da Fonseca; Mariana Furtado Meinberg; Marilene Vale de Castro Monteiro; Matheus Roque; Jorge Milhen Haddad; Rodrigo Aquino Castro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract The overactive bladder (OAB) has a significant negative impact on the quality of life of patients. Antimuscarinics have become the pharmacological treatment of choice for this condition. The objective of this systematic review and meta-analysis is to examine the evidence from randomized clinical trials about the outcomes of the antimuscarinic drugs available in Brazil on OABs. We searched MEDLINE and the Cochrane Central Register of Controlled Trials from the inception of these databases through to September 2015. The primary outcome measures were the mean decrease in urge urinary incontinence episodes and the mean decrease in the frequency of micturition. The results suggest that there is a moderate to high amount of evidence supporting the benefit of using anticholinergic drugs in alleviating OAB symptoms when compared with placebo. It is still not clear whether any of the specific drugs that are available in Brazil offer advantages over the others. These drugs are associated with adverse effects (dry mouth and constipation), although they are not related to an increase in the number of withdrawals.